Statistics for modern business decisions - Lapin, Lawrence L. (New York : Harcourt Brace Jovanovich, 1982)
The book is intended for business statistics courses with a college algebra prerequisite, this text offers unique coverage of Bayesian methods.
Includes index.
Includes bibliographical references: p. 815-817.
aia 25/07/2017
Loans
Keywords: Social sciences; Statistical methods; Commercial statistics; Statistics